2018
DOI: 10.1007/s13204-018-0925-3
|View full text |Cite
|
Sign up to set email alerts
|

Initial growth dynamics of 10 nm nanobubbles in the graphene liquid cell

Abstract: The unexpected long lifetime of nanobubble against the large Laplace pressure is one of the important issues in nanobubble research and a few models have been proposed to explain it. Most studies, however, have been focused on the observation of relatively large nanobubbles over 100 nm and are limited to the equilibrium state phenomena. The study on the sub-100 nm sized nanobubble is still lacking due to the limitation of imaging methods which overcomes the optical resolution limit. Here, we demonstrate the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Because thermal fluctuations govern the smallest stable meniscus, such fluctuations are also likely to play a major role in determining the properties of the critical nucleus. Note that the size of the critical nucleus obtained in this study is comparable to the size of the smallest bubbles observed from an in situ transmission electron microscopy experiment . Given the volume ( V ) and the number of molecules ( N ) in the critical nucleus, the average distance between the gas molecules inside can be estimated via , which yields a distances of ∼5 Å between H 2 molecules and ∼6 Å between both N 2 and O 2 molecules.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Because thermal fluctuations govern the smallest stable meniscus, such fluctuations are also likely to play a major role in determining the properties of the critical nucleus. Note that the size of the critical nucleus obtained in this study is comparable to the size of the smallest bubbles observed from an in situ transmission electron microscopy experiment . Given the volume ( V ) and the number of molecules ( N ) in the critical nucleus, the average distance between the gas molecules inside can be estimated via , which yields a distances of ∼5 Å between H 2 molecules and ∼6 Å between both N 2 and O 2 molecules.…”
Section: Resultssupporting
confidence: 68%
“…Note that the size of the critical nucleus obtained in this study is comparable to the size of the smallest bubbles observed from an in situ transmission electron microscopy experiment. 38 Given the volume (V) and the number of molecules (N) in the critical nucleus, the average distance between the gas molecules inside can be estimated via…”
Section: Resultsmentioning
confidence: 99%
“…In situ transmission electron microscopy (TEM) also allowed probing sub-100 nm NBs next to cathode materials. It allows inferring the 3D shape of the NB over the electrode surface, though the requirements of thin liquid cells strongly affects the NB growth dynamics, which is also strongly influenced by radiolysis effects from the electron beam. , …”
Section: Introductionmentioning
confidence: 99%
“…It allows inferring the 3D shape of the NB over the electrode surface, though the requirements of thin liquid cells strongly affects the NB growth dynamics, which is also strongly influenced by radiolysis effects from the electron beam. 17,18 Optical microscopies provide a pertinent imaging alternative in terms of high throughput and wider field of observation. Recently, the dynamics of EC single NB formation was optically monitored by total internal reflection fluorescence microscopy (TIRFM).…”
Section: Introductionmentioning
confidence: 99%
“…( 5), parameters (A, σ x , σ y , x c , y c ) are chosen uniformly from the ranges in Table II These values are chosen in accordance with previous theoretical literature [24,47]. The random superposition of these deformations produces a net deformation comparable to small graphene nanobubbles observed experimentally, less than 50nm in radius [48][49][50].…”
Section: Analysis Of Network Sizementioning
confidence: 99%